Multi-Omics Reveals That the Rumen Transcriptome, Microbiome, and Its Metabolome Co-regulate Cold Season Adaptability of Tibetan Sheep - Liu, Xiu; Sha, Yuzhu; Lv, Weibing; Cao, Guizhong; Guo, Xinyu; Pu, Xiaoning; Wang, Jiqing; Li, Shaobin; Hu, Jiang; Luo, Yuzhu (Frontiers in Microbiology, 2022)
Tibetan sheep can maintain a normal life and reproduce in harsh environments under extreme cold and lack of nutrition. However, the molecular and metabolic mechanisms underlying the adaptability of Tibetan sheep during the cold season are still unclear. Hence, we conducted a comprehensive analysis of rumen epithelial morphology, epithelial transcriptomics, microbiology and metabolomics in a Tibetan sheep model. The results showed that morphological structure of rumen epithelium of Tibetan sheep in cold season had adaptive changes. Transcriptomics analysis showed that the differential genes were primarily enriched in the PPAR signaling pathway (ko03320), legionellosis (ko05134), phagosome (ko04145), arginine and proline metabolism (ko00330), and metabolism of xenobiotics by cytochrome P450 (ko00980). Unique differential metabolites were identified in cold season, such as cynaroside A, sanguisorbin B and tryptophyl-valine, which were mainly enriched in arachidonic acid metabolism, arachidonic acid metabolism and linolenic acid metabolism pathways, and had certain correlation with microorganisms. Integrated transcriptome-metabolome-microbiome analysis showed that epithelial gene-GSTM3 expression was upregulated in the metabolism of xenobiotics by the cytochrome P450 pathway during the cold season, leading to the downregulation of some harmful metabolites; TLR5 gene expression was upregulated and CD14 gene expression was downregulated in the legionellosis pathway during the cold season. This study comprehensively described the interaction mechanism between the rumen host and microbes and their metabolites in grazing Tibetan sheep during the cold season. Rumen epithelial genes, microbiota and metabolites act together in some key pathways related to cold season adaptation.